Characterization of Burkholderia pseudomallei protein BPSL1375 validates the Putative hemolytic activity of the COG3176 N-Acyltransferase family - Ahmad, Laziana; Teng, Loong Hung; Mat Akhir, Nor Azurah; Rahmah, Mohamed; Nathan, Sheila; Raih, Mohd Firdaus (BioMed Central Ltd, 2015)
Background: There are still numerous protein subfamilies within families and superfamilies that do not yet have conclusive empirical experimental evidence providing a specific function. These proteins persist in databases with the annotation of a specific ‘putative’ function made by association with discernible features in the protein sequence. Results: Here, we report the characterization of one such protein produced by the pathogenic soil bacterium Burkholderia pseudomallei, BPSL1375, which provided evidence for putative hemolysins in the COG3176 family to have experimentally validated hemolytic activity. BPSL1375 can be classified into the N-acyltransferase superfamily, specifically to members of the COG3176 family. Sequence alignments identified seven highly conserved residues (Arg54, Phe58, Asp75, Asp78, Arg99, Glu132 and Arg135), of which several have been implicated with Nacyltransferase activity in previously characterized examples. Using the 3D model of an N-acyltransferase example as a reference, an acyl homoserine lactone synthase, we generated 3D structure models for mutants of six of the seven N-acyltransferase conserved residues (R54, D75, D78, R99, E132 and R135). Both the R99 and R135 mutants resulted in a loss of hemolytic activity while mutations at the other five positions resulted in either reduction or increment in hemolytic activity. Conclusions: The implication of residues previously characterized to be important for N-acyltransferase activity to hemolytic activity for the COG3176 family members of the N-acyltransferase provides validation of the correct placement of the hemolytic capability annotation within the N-acyltransferase superfamily.